BENTUK KEWAJIBAN NEGARA DALAM MELINDUNGI HAK ANAK BAGI ANAK YANG TERLIBAT DALAM KONFLIK BERSENJATA BERDASARKAN KONVENSI JENEWA 1949 DAN KONVENSI HAK ANAK 1989 (STUDI KASUS TENTARA ANAK DI MYANMAR) - Ginanjar Ismu Solikhin; Erna Dyah Kusumawati (Faculty of Law Universitas Sebelas Maret, 2015)
This research aims to determine and to explain Myanmar’s obligations under the 1949 Geneva Conventions and the Convention on the Rights of the Child 1989 to protect the rights of children. This research is a prescriptive normative legal research. This study uses the 1949 Geneva Conventions and the Convention on the Rights of the Child 1989. In addition this study uses Additional Protocol I and II 1977 and Optional Protocol 2000 as its primary legal sources. While literatures, experts oppinions, as well as law journals and study report are used as secondary law sources. The Sources were collected through literature study. The results show that Myanmar’s obligations to protect the rights of children in armed conflict has been regulated in the 1949 Geneva Conventions and the Convention on the Rights of the Child 1989. Some of these obligations have been implemented by Myanmar as a State Regulation, among others, the establishment of national law: Section 374 of the Myanmar Penal Code concerning forced labour. In the military provisions, Myanmar has a regulation namely Directive No. 13/73 (1974) Myanmar Defence Services and War Office Council that sets the prohibition of military recruitment of Underage children. In terms of judicial assistance, Myanmar has formed the National Committee on Children's Rights in order to prevent the recruitment of children. But there are major obligations listed in the action plan which have not been fulfilled by Myanmar, Such as criminal prosecution for the recruiters of children to non-government armed groups, facilitate the UN for an access to all non-governmental armed groups registered for humanitarian purposes dialogue and also ensuring the implementation of the action plan.